Childhood maltreatment and amygdala response to interpersonal threat in a transdiagnostic adult sample: the role of trait dissociation - Seitz, Katja I.; Sicorello, Maurizio; Schmitz, Marius; Valencia, Noel; Herpertz, Sabine; Bertsch, Katja; Neukel, Corinne (Biological psychiatry. Cognitive neuroscience and neuroimaging, 2024)
Background - Childhood maltreatment (CM) confers risk for different mental disorders as well as transdiagnostic symptoms such as dissociation. Aberrant amygdala response to interpersonal threat may link CM to transdiagnostic psychopathology and has recently been shown to depend on type and developmental timing of CM experiences. Still, most studies on CM and threat-related amygdala response employ categorical disorder-specific perspectives and fail to consider type and timing of CM exposure. We aimed to investigate associations between CM, amygdala response to interpersonal threat, and dimensional psychopathological symptoms including trait dissociation in a transdiagnostic adult sample, specifically considering type, timing, and duration of CM. - Methods - We conducted a cross-sectional neuroimaging study in 141 participants with varying levels of CM, including mostly female participants with major depressive disorder (n = 36), posttraumatic stress disorder (n = 34), and somatic symptom disorder (n = 35) and healthy volunteers (n = 36). Participants underwent functional magnetic resonance imaging during an emotional face-matching task, completed the brief German interview version of the Maltreatment and Abuse Chronology of Exposure scale, and answered self-report measures of transdiagnostic CM-related symptoms including trait dissociation. Data were analyzed using a machine learning-based model comparison procedure. - Results - In our transdiagnostic sample, neither type nor timing or duration of CM predicted amygdala response to interpersonal threat. Instead, trait dissociation predicted blunted bilateral amygdala response and emerged as a possible mediator between CM and amygdala function. - Conclusions - Trait dissociation may be an important confounder in the widely documented association between CM and threat-related amygdala response, which should be considered in future longitudinal studies.
Online verfügbar: 26. Januar 2024, Artikelversion: 4. Juni 2024
Gesehen am 22.11.2024